Barricade the King's Highway! Deteriorating Core-Periphery Relations, Mobilization, and Repression in Jordan's Hinterland. Issue 2 (3rd April 2022) - Brown, Daniel P.
ABSTRACT: Even before the Arab Uprising waves, the grievances of increased demands on services and subsidies, shifting economic policy, the deteriorating core-periphery relations between Amman and erstwhile major centers in the Jordanian hinterland (e.g., al-Karak, Maʿān, al-Ṭafilah) have all characterized one aspect of the delicate balance of power in the Hashemite Kingdom. This article will examine the nature of this deterioration, and how the monarchy has variously conceded to, repressed, and thereby withstood repeated protests emanating from the hinterlands. Finally, this article examines a case study of the city of Maʿān as a bellwether hub of popular protest in Jordan.